Live Streaming, Online Customer Review, Cashback Promotion on Product Purchase Interest on Shopee Features - Naeli, Devi; Kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: Analyzing the Influence of Live Streaming, Online Customer Review, Cashback Promotion on Product Purchase Interest on Shopee Features Design/Methode/Approach: Quantitative method with linear regression design is used to test the impact of each feature on product purchase interest. Data collection is done through a survey distributed to consumers who actively shop at Shopee Research Finding : Research This show that live streaming has influence positive and significant to interest buy products , with beta value 0.318 and significance 0.002 (p<0.05). Review online customers also provide impact positive and significant to interest buy products , with beta value 0.282 and significance 0.006 (p<0.05). While that , cashback promotion shows connection positive , although No significant in a way statistics , with beta value 0.210 and significance 0.033 (p>0.05) Theoretical contribution/Originality: This study provides theoretical insights related to understanding the factors that influence purchasing decisions on Shopee features. Practitioner/Policy implications: Live streaming: Marketers should leverage live streaming functionality to increase consumer engagement and purchase intent while ensuring video quality and clarity of information. Online customer reviews: E-commerce platforms should encourage honest and positive customer reviews as reviews have a significant impact on purchasing decisions. Cashback Promotion: While cashback can be an incentive, its impact on purchase intent is not significant, so it should be combined with other more impactful features, such as live streaming or customer reviews. Research limitation: This research was conducted with a limited sample focusing only on management students of the 2021 intake. This is to standardize the results of the entire population of Shopee users or other e-commerce platforms.